Agricultural development project: case of Kenaf industry in ECER - Kamaruddin, Norfaryanti; Othman, Mohd Shahwahid (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
Kenaf industry has being developed in the East Coast Economic Region (ECER) mainly in the area of Kelantan and Terengganu which have a generally agrarian economy dominated by rice, rubber and tobacco. There are six (6) key drivers to accelerate the growth of ECER. Kenaf industry is to be developed under Agriculture key driver where the aim is to increase and sustain farmers‟ income as the AFTA takes effect in 2010 which would be effecting tobacco growers. Kenaf industry development has started as early as 2001, where the Government has committed in financing research and development projects involving Kenaf. The development of a Kenaf industry in Malaysia is projected to create more jobs in rural areas involving about thousands of families. A survey was done to farmers who were planting Kenaf for the last few years in order to capture their perspective towards integrated rural development through ECER projects. Most of the respondents are accepting the development while there are some of them who have different perspectives. According to Factor Analysis result, there are two factors that affect farmers‟ acceptance level towards the kenaf industry in ECER; projects‟ details and implementation as well as supporting effort.